PCB52 exposure alters the neurotransmission ligand-receptors in male offspring and contributes to sex-specific neurodevelopmental toxicity. (September 2020) - Zhao, Dong; Wang, Qi; Zhou, Wen-Tao; Wang, Li-Bin; Yu, Hao; Zhang, Kai-Kai; Chen, Li-Jian; Xie, Xiao-Li
Abstract: Polychlorinated biphenyls (PCBs) in the air are predominantly the less chlorinated congeners. Non-dioxin-like (NDL) low-chlorinated PCBs are more neurotoxic, and cause neurodevelopmental and neurobehavioral alterations in humans. However, the underlying mechanisms for this neurodevelopmental toxicity remain unknown. In the present study, Wistar rats were treated by gavage with PCB52 (1 mg/kg body weight) or corn oil from gestational day 7 to postnatal day 21. Both the body lengths and weights of the suckling rats at birth were significantly decreased by PCB52 treatment, suggesting developmental toxicity. Although no obvious histopathological changes were observed in the brain, using RNA-sequencing, 208 differentially expressed genes (DEGs) were identified in the striatum of PCB52-treated male offspring, while just 13 DEGs were identified in female offspring, suggesting sex-specific effects. Furthermore, using Gene Ontology enrichment analysis, neurodevelopmental processes, neurobehavioral alterations, and neurotransmission changes were enriched from the 208 DEGs in male offspring. Similarly, using Kyoto Encyclopedia of Genes and Genomes enrichment analysis, neuroactive ligand receptor interactions and multiple synapse pathways were enriched in male offspring, implying dysfunction of the neurotransmission system. Reductions in the protein expressions of these ligand receptors were also identified in the striatum, cerebral cortex, and hippocampus using western blotting methods. Taken together, our findings indicate that PCB52 exposure during gestation and lactation results in the abnormal expression of neurotransmission ligand-receptors in male offspring with a sex bias, and that this may contribute to neurodevelopmental toxicity. Graphical abstract: Image 1 Highlights: PCB52 exerted sex-specific effects on nervous system of rat offspring by RNA-sequencing. PCB52 altered multiple neurotransmission ligand-receptors in male offspring of rats. The ligand-receptors alterations might contribute to the neurodevelopmental toxicity.